Absence of Association between Body Size and Deciduous Tooth Size in American Black Children - Loren R. Lease; Edward F. Harris (Dental Anthropology Association, 2001)
Weak positive associations between tooth size and body size have been documented for the permanent dentition. Presumably, if the deciduous dentition were under the same genetic controls as the permanent, there would also be a discernable association for the deciduous teeth in young children. The deciduous dentition of 133 modern American Black children was examined to determine the correlations between body size and tooth size. The results, based on Spearman's rank-order correlations, disclosed no statistically significant association with body weight or stature, expressed as age- and sex-specific centiles, and crown diameters at the alpha level of 0.05. It is speculated that maternal influences - which modulate perinatal growth of the offspring - dissociate the tooth size - body size association in children, whereas the individuals' own genotypes are relatively more strongly expressed with increasing age.